Evaluation of the utility of 99mTc‐MDP bone scintigraphy versus MIBG scintigraphy and cross‐sectional imaging for staging patients with neuroblastoma. Issue 11 (27th April 2017) - Gauguet, Jean‐Marc; Pace‐Emerson, Tamara; Grant, Frederick D.; Shusterman, Suzanne; DuBois, Steven G.; Frazier, A. Lindsay; Voss, Stephan D.
Abstract: Purpose: Accurate staging of neuroblastoma requires multiple imaging examinations. The purpose of this study was to determine the relative contribution of 99m Tc‐methylene diphosphonate (MDP) bone scintigraphy (bone scan) versus metaiodobenzylguanidine scintigraphy (MIBG scan) for accurate staging of neuroblastoma. Methods: A medical record search by the identified patients with neuroblastoma from 1993 to 2012 who underwent both MIBG and bone scan for disease staging. Cross‐sectional imaging was used to corroborate the scintigraphy results. Clinical records were used to correlate imaging findings with clinical staging and patient management. Results: One hundred thirty‐two patients underwent both MIBG and bone scan for diagnosis. All stage 1 (n = 12), 2 (n = 8), and 4S (n = 4) patients had a normal bone scan with no skeletal MIBG uptake. Six of 30 stage 3 patients had false (+) bone scans. In the 78 stage 4 patients, 58/78 (74%) were both skeletal MIBG(+)/bone scan (+). In 56 of the 58 cases, skeletal involvement detected with MIBG was equal to or greater than that detected by bone scan. Only 3/78 had (–) skeletal MIBG uptake and (+) bone scans; all 3 had other sites of metastatic disease. Five of 78 had (+) skeletal MIBG with a (–) bone scan, while 12/78 had no skeletal involvement by either MIBG or bone scan. In no case did a positive bone scan alone determine a stage 4 designation. Conclusion: In the staging of neuroblastoma, 99m Tc‐MDP bone scintigraphy does not identify unique sites of disease that affect disease stage or clinical management, and in the majority of cases bone scans can be omitted from the routine neuroblastoma staging algorithm.